Managing no-reflow during percutaneous coronary intervention. (August 2012) - Derntl, Michael; Weidinger, Franz
Visible impairment of epicardial coronary flow associated with ischemia may occur during percutaneous coronary intervention (PCI). This so called no-reflow phenomenon is found despite any evidence for distal embolic cutoff, obstruction or vessel dissection. It occurs in patients who undergo PCI, typically of a lesion responsible for recent myocardial infarction, or treatment of a saphenous vein graft. Various mechanisms leading to microvascular obstruction induce no-reflow. No-reflow has a strong negative impact on clinical outcome. Administration of adenosine, a calcium-channel blocker, or nitroprusside is appropriate to treat PCI-related no-reflow that occurs during primary or elective PCI. In the setting of acute myocardial infarction, evidence for a beneficial effect on no-reflow also exists for abciximab and nicorandil. Thrombectomy and/or embolic protection devices should be used for the prevention of no-reflow in the setting of high thrombus burden and during saphenous vein graft intervention.